Studi Korelasi Self Awareness dengan Tingkat Pemahaman Materi Kuliah Selama Pembelajaran Daring dalam Masa Pandemi Covid-19 pada Mahasiswa STIKes Bethesda Yakkum Yogyakarta - Tri Wahyuni Ismoyowati (FORIKES, 2021)
The success of online learning during the Covid-19 pandemic depends on the discipline of all parties. Educational institutions need to create a scheme by developing good management in regulating the online learning system. The purpose of this study was to determine the relationship between self-awareness and the level of understanding of lecture material during online learning during the Covid-19 Pandemic in STIKes Bethesda Yakkum Yogyakarta students. This study uses a correlation study method with a cross-sectional approach. The population in the study were students of STIKes Bethesda YAKKUM Yogyakarta, Diploma 3 Study Program Levels I and II, and Bachelor of Nursing Study Program totaled 172 students. The measuring instrument in this study is a self-awareness and level of understanding questionnaire. Validity test showed r > 0.444 and reliability showed 0.459 to 0.953. Majority 21-25 years old 84.9%, female 81.4%, undergraduate nursing 71.5%. Self Awareness majority is 92.4%, the level of understanding is 55.2%. The p value (0.023) is that there is a relationship between self-awareness and the level of understanding of lecture material during online learning during the Covid-19 pandemic. So the assumption of the researcher is that the higher the self-awareness, the higher the level of student understanding of the material obtained by the online learning method. Keywords: self awareness; online; understanding; Covid-19 pandemic ABSTRAK Kesuksesan pembelajaran daring selama masa pandemi Covid-19 tergantung pada kedisiplinan semua pihak. Institusi pendidikan perlu membuat skema dengan menyusun manajemen yang baik dalam mengatur sistem pembelajaran daring. Tujuan dalam penelitian ini adalah untuk mengetahui hubungan antara self awareness dengan tingkat pemahaman terhadap materi kuliah selama pembelajaran daring dalam masa Pandemi Covid-19 pada mahasiswa STIKes Bethesda Yakkum Yogyakarta. Penelitian ini menggunakan metode studi korelasi dengan pendekatan cross-sectional. Populasi pada penelitian mahasiswa STIKes Bethesda YAKKUM Yogyakarta Prodi Diploma 3 Tingkat I dan II, serta Prodi Sarjana Keperawatan berjumlah 172 mahasiswa. Alat ukur dalam penelitian ini adalah kuesioner self awareness dan tingkat pemahaman. Uji validitas menunjukkan r >0,444 dan reliabilitas menunjukkan 0,459 sampai 0,953. Mayoritas 21-25 tahun 84,9%, perempuan 81,4%, sarjana keperawatan 71,5%. Self Awareness mayoritas sedang 92,4%, tingkat pemahaman sedang 55,2%. Nilai p value (0,023) yaitu terdapat hubungan self awareness dengan tingkat pemahaman materi kuliah selama pembelajaran daring dalam masa pandemi Covid-19. Sehingga asumsi peneliti adalah semakin tinggi self awareness, semakin tinggi tingkat pemahaman mahasiswa tentang materi yang didapatkan dengan metode pembelajaran daring. Kata kunci: self awareness; daring; pemahaman; pandemi Covid-19